Bindarit inhibits human coronary artery smooth muscle cell proliferation, migration and phenotypic switching. - Marcella Maddaluno (PLoS ONE, 2012)
Bindarit, a selective inhibitor of monocyte chemotactic proteins (MCPs) synthesis, reduces neointimal formation in animal models of vascular injury and recently has been shown to inhibit in-stent late loss in a placebo-controlled phase II clinical trial. However, the mechanisms underlying the efficacy of bindarit in controlling neointimal formation/restenosis have not been fully elucidated. Therefore, we investigated the effect of bindarit on human coronary smooth muscle cells activation, drawing attention to the phenotypic modulation process, focusing on contractile proteins expression as well as proliferation and migration. The expression of contractile proteins was evaluated by western blot analysis on cultured human coronary smooth muscle cells stimulated with TNF-α (30 ng/mL) or fetal bovine serum (5%). Bindarit (100-300 µM) reduced the embryonic form of smooth muscle myosin heavy chain while increased smooth muscle α-actin and calponin in both TNF-α- and fetal bovine serum-stimulated cells. These effects were associated with the inhibition of human coronary smooth muscle cell proliferation/migration and both MCP-1 and MCP-3 production. The effect of bindarit on smooth muscle cells phenotypic switching was confirmed in vivo in the rat balloon angioplasty model. Bindarit (200 mg/Kg/day) significantly reduced the expression of the embryonic form of smooth muscle myosin heavy chain, and increased smooth muscle α-actin and calponin in the rat carodid arteries subjected to endothelial denudation. Our results demonstrate that bindarit induces the differentiated state of human coronary smooth muscle cells, suggesting a novel underlying mechanisms by which this drug inhibits neointimal formation.